2016
DOI: 10.1016/j.celrep.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry Breaking in an Edgeless Epithelium by Fat2-Regulated Microtubule Polarity

Abstract: Planar cell polarity (PCP) information is a critical determinant of organ morphogenesis. While PCP in bounded epithelial sheets is increasingly well-understood, how PCP is organized in tubular and acinar tissues is not. Drosophila egg chambers (follicles) are an acinus-like ‘edgeless epithelium’ and exhibit a continuous, circumferential PCP that does not depend on pathways active in bounded epithelia; this follicle PCP directs formation of an ellipsoid rather than a spherical egg. Here we apply a novel imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 32 publications
2
60
0
Order By: Relevance
“…Fat2 (aka Kugelei) shows a planar polarized distribution at the basal surface, such that it is present on cell-cell interfaces roughly perpendicular to the direction of tissue motility, and is absent from the lateral cell-cell interfaces (Viktorinova et al, 2009) (Figure 1H). It was later shown that this localization corresponds to each cell’s trailing edge and that Fat2 is required for collective follicle cell migration (Cetera et al, 2014; Chen et al, 2016; Viktorinová and Dahmann, 2013). A recent model proposed that Fat2 promotes epithelial motility by stimulating the formation of leading edge protrusions on a cell-autonomous basis (Squarr et al, 2016); however, how this model fits with Fat2’s trailing edge localization is unclear.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fat2 (aka Kugelei) shows a planar polarized distribution at the basal surface, such that it is present on cell-cell interfaces roughly perpendicular to the direction of tissue motility, and is absent from the lateral cell-cell interfaces (Viktorinova et al, 2009) (Figure 1H). It was later shown that this localization corresponds to each cell’s trailing edge and that Fat2 is required for collective follicle cell migration (Cetera et al, 2014; Chen et al, 2016; Viktorinová and Dahmann, 2013). A recent model proposed that Fat2 promotes epithelial motility by stimulating the formation of leading edge protrusions on a cell-autonomous basis (Squarr et al, 2016); however, how this model fits with Fat2’s trailing edge localization is unclear.…”
Section: Introductionmentioning
confidence: 98%
“…The basal epithelial surface contacts a basement membrane ECM that ensheaths the egg chamber. From the time an egg chamber forms until stage 8 of oogenesis, the follicle cells collectively migrate along their basement membrane (Cetera et al, 2014; Chen et al, 2016; Haigo and Bilder, 2011). This migration causes the egg chamber to rotate within its surrounding ECM, which remains stationary (Haigo and Bilder, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…MTs near the basal epithelial surface are aligned in the direction of movement both before and during migration, with MT plus-end growth biased toward the trailing edge of each cell [30,36]. dFat2 is required both for the biased plus-end growth and for tissue-level MT alignment at different developmental stages [30,36], and dFat2’s ICD mediates its role in MT alignment [37]. Although the follicular epithelium always migrates perpendicular to the egg chamber’s anterior-posterior axis, this migration can occur in either a clockwise or counterclockwise direction [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although the follicular epithelium always migrates perpendicular to the egg chamber’s anterior-posterior axis, this migration can occur in either a clockwise or counterclockwise direction [25]. The observation that dFat2 biases the direction of MT plus-end growth before migration begins has led to the proposal that dFat2 helps to determine which way the epithelium will go [30,36]. Given that dFat2’s trailing edge localization also depends on MTs, it has also been proposed that dFat2 may promote both epithelial motility and its own localization through a MT-dependent feedback amplification loop [30,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation